Jordan : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This Selected Issues paper investigates the macroeconomic impact of the Syria crisis on Jordan. It is indicated that the crisis: (1) had an overall negative impact on measured output growth-although anecdotal evidence suggests possibly a positive impact on output in the informal sector; (2) contributed to inflationary pressures, particularly on rents; and (3) strained labor markets, mostly in the informal sector as refugees compete with locals for jobs. Although the crisis has put a strain on the external trade balance, the overall impact on the current account is not clear.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet